Frida Kahlo and Her Animalitos - Brown, Monica 1969-; Parra, John (New York North South Books, 2017)
Containing a biography in narrative format, the artist Frida Kahlo's love of her pets and painting them is explored.
Keywords: Kahlo, Frida -- Juvenile literature; Kahlo, Frida; Painters -- Biography -- Mexico; Animals in art -- Juvenile literature; Painters -- Biography -- Mexico; Animals in art; Biographies